Extensive marine anoxia in the European epicontinental sea during the end-Triassic mass extinction - He, Tianchen; Wignall, Paul B.; Newton, Robert J.; Atkinson, Jed W.; Keeling, Jacob F.J.; Xiong, Yijun; Poulton, Simon W. (Global and planetary change, 2022)
Warming-induced marine anoxia has been hypothesized as an environmental stressor for the end-Triassic mass extinction (ETME), but links between the spread of marine anoxia and the two phases of extinction are poorly constrained. Here, we report iron speciation and trace metal data from the Bristol Channel Basin and Larne Basin of the NW European epicontinental sea (EES), spanning the Triassic–Jurassic (T–J) transition (~ 202–200 Ma). Results show frequent development of anoxic-ferruginous conditions, interspersed with ephemeral euxinic episodes in the Bristol Channel Basin during the latest Rhaetian, whereas the contemporaneous Larne Basin remained largely oxygenated, suggesting heterogeneous redox conditions between basins. Subsequently, more persistent euxinic conditions prevailed across the T–J boundary in both basins, coinciding precisely with the second phase of the ETME. We propose that this later phase of benthic faunal loss in the NW EES was directly driven by the bottom-water oxygen crisis. Conversely, although anoxic conditions persisted into the early Hettangian, the benthos diversified at this time in nearshore areas. Post-extinction conditions were poised at a fluctuating redox state, but anoxia did not extend into the shallowest areas where benthic marine ecosystem recovery was occurring. •Water column anoxia was common in the European epicontinental sea through the Triassic–Jurassic transition.•Intensified marine euxinia developed at the second phase of the end-Triassic mass extinction.•A low oxygen ocean persisted post-extinction, but with a fluctuating redox state and limited ecological influence.